Association Between Urinary Stress Incontinence and Levator Avulsion Detected by 3D Transperineal Ultrasound - Zhong, Chunyan; Hu, Pan; Ran, Suzhen; Tang, Jing; Xiao, Chunmei; Lin, Yun; Zhang, Xiaohang; Rong, Yao; Liu, Mingbo (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose To determine the association between levator avulsion and urinary stress incontinence (USI) by 3/4D transperineal ultrasound.Materials and Methods 842 patients who were admitted to our hospital from 2016 to 2019 were recruited for our study. 3D/4D transperineal ultrasound was performed. After standard interview and clinical evaluation, general conditions and levator hiatus data were collected and measured to compare with each group. The odds ratio (OR) of USI symptoms or ultrasound features with levator avulsion were calculated.Results A total of 593 women were studied: 204 suffered from levator avulsion (96 cases of left-side avulsion, 80 cases of right-side avulsion and 28 cases of bilateral avulsion) and 389 women had no avulsion. The gravidity and episiotomy conditions of the avulsion groups were significantly different from the no-avulsion group. Significant differences were found in the transverse diameters and anteroposterior diameters between the levator avulsion group and the no-avulsion group, but there was no difference among the avulsion groups, regardless of whether the patient was at rest or performing the Valsalva maneuver. Interestingly, a significant difference was found in the presence of USI symptoms between the uni-avulsion group and the no-avulsion group. The odds ratio (OR) of USI symptoms in the uni-avulsion group is 2.786 (95 %CI, 1.663–4.669), but 0.939 (95 %CI, 0.276–3.199) for the bilateral avulsion and no-avulsion groups.Conclusion Unilateral levator avulsion may be a risk factor for urinary stress incontinence.
Keywords: transperineal ultrasound; urinary stress incontinence; levator ani avulsion; Gynecology